The added value of the school of the 21st century when combined with a statewide preschool program. - Ginicola, Misty; Finn-Stevenson, Matia; Zigler, Edward (The American journal of orthopsychiatry, 2013)
Although schools have begun to employ multiple programs to reach educational goals, little attention has been paid to the efficacy of combining separate programs. The present study investigates the combination of a school reform model, the School of the 21st Century (21C), and the Arkansas Better Chance (ABC) program, where preschools apply for state funds to provide high quality services to children at risk. To determine if 21C adds anything to the ABC program, the present study compared results from a developmental assessment. The authors compared school-based preschools that had both ABC and 21C services to those programs that offered only ABC services. Results indicated that, at baseline, children within the 21C/ABC programs scored the same or poorer than their ABC-only counterparts. However, at the end of the year, participants at 21C/ABC preschools were significantly ahead of ABC-only programs on all developmental indicators. There were also differences favorable to 21C/ABC preschools between the programs' quality ratings as measured by the Early Childhood Environmental Rating Scale. Copyright © 2013 American Orthopsychiatric Association.
Keywords: *Early Intervention, Educational; *Schools; Arkansas; Arkansas Better Chance program; Child care; Child, Preschool; Early Intervention (Education); Educational Status; Family support; Female; Humans; Male; Poverty; Preschool children; School children; School readiness; Schools; The School of the 21st Century; article; child; dept.csp; education program; female; history; human; male; preschool child; rating scale; school